2010
DOI: 10.3109/11038128.2010.510205
|View full text |Cite
|
Sign up to set email alerts
|

Occupational performance, pain, and global quality of life in women with upper extremity fractures

Abstract: To examine pain, occupational performance problems, and quality of life (QoL) and possible associations between these variables, 41 elderly women with acute pain due to a fracture of the upper extremity were assessed with COPM, DASH, validated questions on pain, and a global question on QoL. The participants reported 802 performance problems: 38% within self-care, 52% within productivity, and 10% within leisure. Strength demanding bilateral activities in cleaning, hygiene, and cooking were most frequently repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…That limitations in self-care were particularly prevalent was also shown in a study using focus group interviews with participants with persistent pain (1). In contrast, one other study using COPM on participants with pain and one study including pain patients but also participants with other diagnoses have shown occupational problems to be more frequent in the productivity category (10,29).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…That limitations in self-care were particularly prevalent was also shown in a study using focus group interviews with participants with persistent pain (1). In contrast, one other study using COPM on participants with pain and one study including pain patients but also participants with other diagnoses have shown occupational problems to be more frequent in the productivity category (10,29).…”
Section: Discussionmentioning
confidence: 83%
“…Several studies reporting frequencies of occupational problems using the COPM have been published (10,(29)(30). One of these (10) was similar to the present study with regard to type of participants (mixed pain diagnoses and mostly women) and rehabilitation setting (specialized pain rehabilitation at university hospital).…”
Section: Discussionmentioning
confidence: 99%
“…The DASH score was interpreted according to Moore as follows: no disability (0), minimal disability (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), mild disability (21-40), moderate disability (41-60), severe disability (61-80), very severe disability (81-100) (17).…”
Section: Disabilitymentioning
confidence: 99%
“…At the time of cast removal, occupational performance among these women has been explored. The nature and number of performance problems have been described in detail, and a high pain score has been found to correlate with the number of performance problems detected on the client-centred assessment tool COPM (1,2). Occupational therapists share the common experience that the performance of activities which is restricted after a DRF often normalizes as the pain lessens and as range of motion and muscle strength improve.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation